PELATIHAN SHOULDER GIRDLE DYNAMIC STABILIZATION LEBIH BAIK DARIPADA PELATIHAN PRONE SCAPULAR STABILIZATION DALAM MENINGKATKAN KEMAMPUAN FUNGSIONAL BAHU PASCA CEDERA SWIMMER SHOULDER PADA ATLET RENANG GAYA BEBAS DI KALIMANTAN BARAT - Myranti Puspitaningtsya Junaedi; I Putu Gede Adiatmika; S. Indra Lesmana; Ketut Tirtayasa; I Wayan Weta; Wahyuddin - (Sport and Fitness Journal, 2019)
ABSTRACTBackground: High duration of training performed by swimmers with dominant freestyle stroke, resulted in significant number of shoulder rotation movement. The presence of continous movement that occurs in the shoulder of swimmers can cause the risk of shoulder injury, known as swimmer’s shoulder. The presence of shoulder injuries among swimmers resulting a decrease in functional ability on the shoulder of swimmers. The training of shoulder girdle dynamic stabilization and prone scapular stabilization is a training that can be used to improve the functional ability among swimmers shoulders. Method: This study used randomized pre test and post test control group design. This study performed on 20 swimmers that diagnosed of swimmer shoulder injury which divided into 2 groups. Treatment Group was given shoulder girdle dynamic stabilization and Control Group was given prone scapular stabilization training. Shoulder functional ability was measured using SPADI and analized on each group. Result: This research showed that every functional training that was given to each sample groups giving an effect to improving shoulder functional ability post swimmer’s shoulder injury among swimmers. There are significant alteration in Treatment Group and Control Group from pre to post test, both was obtained (p< 0.001). There is significant difference from post test between Treatment Group and Control Group, came with (p=0.001). Conclusion: Shoulder girdle dynamic stabilization better than prone scapular stabilization training in improving the functional ability of the shoulder post swimmer shoulder injury among freestyle stroke swimmer athlete in West Kalimantan. Keywords: swimmer’s shoulder injury, shoulder girdle dynamic stabilization, prone scapular stabilization, SPADI